Effects of a tele-prehabilitation program or an in-person prehabilitation program in surgical candidates awaiting total hip or knee arthroplasty: Protocol of a pilot single blind randomized controlled trial - Doiron-Cadrin, Patrick (Contemp Clin Trials Commun, 2016)
BACKGROUND: The accessibility for total joint arthroplasty often comes up against long wait lists, and may lead to deleterious effects for the awaiting patients. This pilot single blind randomized controlled trial aims to evaluate the impact of a telerehabilitation prehabilitation program before a hip or knee arthroplasty compared to in-person prehabilitation or to usual wait for surgery. METHODS/DESIGN: Thirty-six patients on a wait list for a total hip or knee arthroplasty will be recruited and randomly assigned to one of three groups. The in-person prehabilitation group (n = 12) will receive a 12-week rehabilitation program (2 sessions/week) including education, exercises of the lower limb and cardiovascular training. Patients in the tele-prehabilitation group (n = 12) will receive the same intervention using a telecommunication software. The control group (n = 12) will be provided with the hospital's usual documentation before surgery. The Lower Extremity Functional Scale (LEFS) will be the primary outcome measure taken at baseline and at 12 weeks. Secondary measures will include self-reported function and quality of life as well as performance tests. A mixed-model, 2-way repeated-measure ANOVA will be used to analyse the effects of the rehabilitation programs. DISCUSSION: This pilot study is the first to evaluate the feasibility and the impact of a telerehabilitation prehabilitation program for patients awaiting a total joint arthroplasty. The results of this pilot-RCT will set the foundations for further research in the fields of rehabilitation and tele-medicine for patients suffering from lower limb osteoarthritis. TRIAL REGISTRATION: ClinicalTrials.gov: NCT02636751.